Gambaran Kecerdasan Emosi pada Remaja di Pulau Jawa dan Bali - Debora Basaria (Provitae: Jurnal Psikologi Pendidikan, 2019)
Adolescence is a period of transition from childhood to adulthood. Adolescence is a good time to develop emotional intelligence which is one of the important types of intelligence in society (especially in Indonesia). Increasing the adolescent's violence cases who reach 50 percent can cause by emotion regulation problems that occur in these adolescents. Emotional intelligence is one aspect that represents special competencies to facilitate, process, and manage emotionally. The purpose of this study was to obtain an overview of emotional intelligence in adolescents in Java and Bali. The subjects of this study were 1,013 adolescents who came from junior high and high school in Java and Bali and with an age range between 12-19 years. Type of this research is quantitative descriptive research. The results of the normality test of emotional intelligence variables show that research data is normally distributed. The main data processing results can conclude that the majority of adolescents in Java and Bali have controlling intelligence with a moderate level (46%), while the balance between the number of adolescents who have a low level of emotional intelligence (26.9%) and high level of emotional intelligence (26.9%).